2019
DOI: 10.1103/physreva.99.063608
|View full text |Cite
|
Sign up to set email alerts
|

Momentum correlations of a few ultracold bosons escaping from an open well

Abstract: The dynamical properties of a one-dimensional system of two and three bosons escaping from an open potential well are studied in terms of the momentum distributions of particles. In the case of a two-boson system, it is shown that the single-and two-particle momentum distributions undergo a specific transition as the interaction strength is tuned through the point where tunneling switches from the pair tunneling to the sequential one. Characteristic features in the momentum spectra can be used to quantitativel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 90 publications
0
10
0
Order By: Relevance
“…First, we shed some light on the effect of a split barrier on the decay properties of one particle being initially in the lowest energy state, Eq. (25). Our results are shown in Fig.…”
Section: A Single-particle Casementioning
confidence: 62%
See 1 more Smart Citation
“…First, we shed some light on the effect of a split barrier on the decay properties of one particle being initially in the lowest energy state, Eq. (25). Our results are shown in Fig.…”
Section: A Single-particle Casementioning
confidence: 62%
“…New advance in experimental techniques has provided the opportunities to study tunnelling phenomena in a controllable way [20][21][22], which has accelerated research activity towards a better understanding of the properties of unstable manybody states. For instance, the recent studies include systems of two identical non-interacting particles [23], ultracold atom systems [24][25][26][27][28][29][30][31], two-particle systems with Coulomb interactions [32] and a model system consisting of a core-nucleus and two valence protons [33]. It is worth mentioning that the complex scaling method [34] also provides a tool for studying the resonance states of many-particle systems [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…where V 0 and α are controlled experimentally while ξ is the dimensionless position, was deeply studied in [388] and [389]. Finally, the decay problem for attractively interacting bosons was analyzed recently in [390,391]. In these works, it was shown that, depending on the attraction strength, different tunneling processes dominate in the dynamics of the system.…”
Section: Tunneling To the Open Spacementioning
confidence: 99%
“…For example, perfect correlations between opposite momenta, was predicted by Bogoliubov theory in weakly interacting systems [9] and identified to be a hallmark of Bose-Einstein condensation [17,18]. Among others, correlations in momentum space have be shown to be useful for analyzing phenomena such as dynamical Casimir effect [19], Hawking radiation [20][21][22][23][24] or the escape from a barrier [25]. In this paper, we study the fluctuations of the momentum occupation number np in a gas of one-dimensional bosons in the Tonks-Girardeau limit at zero and finite temperature in a harmonic trap.…”
Section: Introductionmentioning
confidence: 99%
“…This is why the community is now studying higher moments of the momentum occupation number, like its variance N 2 p − N p 2 , covariance N p N q [11][12][13][14][15] or even the full distribution (full counting statistics) [14]. This can be a great help for unraveling different regimes [11,16,17] or to identify exotic phenomena like the dynamical Casimir effect [18] or Hawking radiation for instance [19][20][21][22][23]. The data represent a single shot measurement whereas the full line is the average Np .…”
Section: Introductionmentioning
confidence: 99%